Kebijakan Hapus Buku dan Hapus Tagih dalam Penyelesaian Kredit Macet Perbankan - Nanang Tri Budiman (JURNAL RECHTENS, 2015)
Along with the development of economic activities it is increasingly felt the need for sources of funds to finance business activities in the form of loans. In the implementation of the loan repayment, the Customer debtors obtain credit from banks is not fully restore their credit worthiness and timely. On the settlement of problem loans, there are some steps that can be taken by creditors so that the creditors can obtain the loans that have been disbursed to borrowers through credit facilities, among others, the implementation of policies to conditional write off and absolute write off against the granting of credit to borrowers who have bad credit. Remove the book is done by issuing the credit portfolio of the bank bookkeeping and still charged while delete is done by issuing a promissory loan portfolio of bookkeeping and eliminate bank collection rights against the debtor